Edukasi Masyarakat Terhadap Proteksi Bahaya Sistem Kelistrikan Pada Rumah - Bayu Purnomo; Pratama, Ilham (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
One of the dangers in electricity is heat explosions, hot gas and liquid metal caused by short circuits in equipment connected to the voltage source system. In general, this occurs as a result of a lack of knowledge regarding how to maintain electricity and the public's knowledge regarding appropriate electrical materials for use in the household. The purpose of community service. Periodic Inspection and Maintenance. Teach the public to carry out regular inspections and maintenance on electrical installations, such as checking worn cables, loose sockets and protection devices. Use of Personal Protective Equipment (PPE). Provide information regarding the appropriate use of PPE, such as gloves or special footwear when carrying out maintenance or handling electrical equipment. Use electrical equipment that complies with safety standards and is of high quality, and ensure that the installation is carried out by experts. Education and preventing the dangers of the electrical system in the home is a long-term investment to maintain the safety and security of the community. Consistent implementation of this education and implementation of preventive mechanisms will help reduce the risk of electrical hazards in the home. Electrical system hazard detection provides education to the public in choosing the right materials for use in the household